2015
DOI: 10.1242/dev.127191
|View full text |Cite
|
Sign up to set email alerts
|

Escape of X-linked miRNA genes from meiotic sex chromosome inactivation

Abstract: Past studies have indicated that transcription of all X-linked genes is repressed by meiotic sex chromosome inactivation (MSCI) during the meiotic phase of spermatogenesis in mammals. However, more recent studies have shown an increase in steady-state levels of certain X-linked miRNAs in pachytene spermatocytes, suggesting that either synthesis of these miRNAs increases or that degradation of these miRNAs decreases dramatically in these cells. To distinguish between these possibilities, we performed RNA-FISH t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 54 publications
1
19
2
Order By: Relevance
“…Previous studies have shown that the X Chromosome of mouse and opossum is enriched for recently expanded testis-expressed miRNA families, whereas no similar enrichment exists for the chicken Z Chromosome (Guo et al 2009;Meunier et al 2013). The mechanistic basis of this phenomenon has been a matter of intense study (Song et al 2009;Royo et al 2015;Sosa et al 2015). As previously noted, the surplus of X-linked, testis-biased miRNAs in both mouse and opossum was clearly visible also in our data ( Fig.…”
Section: Resultssupporting
confidence: 80%
“…Previous studies have shown that the X Chromosome of mouse and opossum is enriched for recently expanded testis-expressed miRNA families, whereas no similar enrichment exists for the chicken Z Chromosome (Guo et al 2009;Meunier et al 2013). The mechanistic basis of this phenomenon has been a matter of intense study (Song et al 2009;Royo et al 2015;Sosa et al 2015). As previously noted, the surplus of X-linked, testis-biased miRNAs in both mouse and opossum was clearly visible also in our data ( Fig.…”
Section: Resultssupporting
confidence: 80%
“…The authors also showed that the highest expression was detected in Sertoli cells, but this result is not consistent with any of the data previously reported by multiple independent groups using different methodologies including qPCR [3], RNA-FISH [9,10], and RNA-seq [6,11], all showing that these miRNAs are predominantly expressed in germ cells, especially in spermatogonia [6,[9][10][11], and that levels of these miRNAs are extremely low in Sertoli cells [11]. First, qPCR analyses of miR-506 family miRNAs were performed using Sertoli cells and interstitial cells purified from adult mouse testes as well as germ cells of unknown sources with unknown purity.…”
contrasting
confidence: 74%
“…RT-PCR and qPCR results revealed that Rpl10 is broadly expressed in different tissues with similar expression levels between male and female mice, except for a relatively lower expression in testis ( Figures S3A and S3B). Considering that Rpl10 may be subject to meiotic sex chromosome inactivation (MSCI), which results in the transcriptional silencing of most protein-coding genes on the sex chromosomes from the pachytene stage until spermiogenesis [11,[41][42][43][44], we examined the expression dynamics of Rpl10 in mouse germ cell populations isolated by STA-PUT ( Figures S3C and S3D). RT-PCR analysis showed that the expression level of Rpl10 was comparable in spermatogonia and early spermatocytes (preleptotene to zygotene) but sharply reduced in late spermatocytes (pachytene and diplotene) and round spermatids ( Figure 3A), indicating transcriptional silencing of Rpl10 during and after MSCI.…”
Section: Rpl10 Expression Is Subject To Meiotic Sex Chromosome Inactimentioning
confidence: 99%